Learn how anti‐doping legislation potentially impacts college athletics administrators. Issue 5 (5th August 2021) - Massaro, Paul; Tygart, Travis T.; Neal, Timothy; Wright, Ken
Abstract : As a college athletics administrator, general counsel, or risk manager, you should be aware of certain potential acts by athletics staff or coaches that could result in not only a governing body rules violation, but could also lead to criminal charges and devastating public relations for your institution. Many believe that terrible outcomes for athletics departments can only result from NCAA violations or when athletics staff or coaches commit felonies at the state level. However, a federal law passed in 2019 that imposes severe penalties related to drug doping activity by athletics staff should catch the attention of athletics administrators, legal counsel, and risk management staff.